A new method for predicting viscosity of pure organic liquids - (:unkn) unknown (CANADIAN SOC CHEMICAL ENGINEERING, 1998)
A new semi-theoretical method based on Enskog's hard sphere theory for dense fluids and the principle of corresponding stales is presented for predicting viscosity of pure organic liquids. The viscosities of 75 organic liquids - 37 acyclic and 38 cyclic hydrocarbons - were calculated using this method which requires critical properties and normal boiling point as input data. The predictions were compared with empirical data and other prediction methods. Highly satisfactory results were obtained over a wide range of temperatures (0.45 < T-r < 0.80).
Keywords: organic liquid viscosity; prediction of organic liquid viscosity; FLUID TRANSPORT-COEFFICIENTS; THERMAL-CONDUCTIVITY; MULTIPARAMETER CORRELATION; CORRESPONDING-STATES; HYDROCARBONS; MIXTURES; TEMPERATURE; EQUATION; MODEL